2002
DOI: 10.1002/cncr.10915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporine on hematopoietic and immune functions in patients with hypoplastic myelodysplasia

Abstract: BACKGROUNDImmunosuppression may benefit some patients with hypoplastic myelodysplasia (HMDS) and refractory anemia (RA), but its mechanism of action is still obscure.METHODSUsing flow cytometry, we studied Fas‐receptor (Fas‐R), Fas‐ligand (Fas‐L), and interferon‐γ (IFN‐γ) expression in CD34+ cells and lymphocytes obtained from 11 HMDS and 20 RA patients. In colony assays and long‐term cultures, the effects of Fas triggering, IFN‐γ blockade, or cyclosporine(CsA) on the growth of hematopoietic progenitors (colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 63 publications
(191 reference statements)
0
31
1
Order By: Relevance
“…Furthermore, IFN-␥ produced by human stromal microenvironment has been demonstrated to negatively affect hemopoiesis (16,47). In agreement with this, IFN-␥ inhibits the in vitro growth of hemopoietic progenitors, including primitive human CD34 ϩ…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, IFN-␥ produced by human stromal microenvironment has been demonstrated to negatively affect hemopoiesis (16,47). In agreement with this, IFN-␥ inhibits the in vitro growth of hemopoietic progenitors, including primitive human CD34 ϩ…”
Section: Discussionmentioning
confidence: 70%
“…Clinical and experimental studies have strongly implicated IFN-␥ as a key mediator of BM failure in a number of diseases associated with inflammation, such as graft-vs-host disease, myelodysplasic syndromes, and aplastic anemia (10,11,21,47), and recent studies suggest that the ability of drugs, such as cyclosporine, to inhibit IFN-␥ production might explain their beneficial effects on hemopoiesis in patients with immune-mediated BM suppression (47). Furthermore, IFN-␥ produced by human stromal microenvironment has been demonstrated to negatively affect hemopoiesis (16,47).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these studies showed that the p38 MAPK pathway is essential for the generation of the growth-inhibitory effects of IFN-a on leukemic progenitors, consistent with our previous observations in studies using SB203580 (11). TNF-a is overproduced in certain disease states and has been implicated in the pathogenesis of bone marrow failure syndromes and MDS (22)(23)(24)(25)(26)(27). We sought to examine the activation of the p38 MAPK pathway by TNF-a in hematopoietic cells and to identify downstream effectors of this signaling cascade that may be participating in the generation of TNF-a responses.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these cytokines have been implicated in the pathophysiology of MDS and other bone marrow failure disorders, including ACD (22)(23)(24)(25)(26)(27). Therefore, we considered the possibility that pharmacologic inhibitors of the p38 MAPK pathway may reverse the suppressive effects of these cytokines in the bone marrows of patients with MDS and ACD, in which bone marrows there is abnormal cytokine overproduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation